Neraca Massa, Komposisi Kimia dan Nilai Ekonomis PengolahanAgroindustri Glukomanan - M Fatoni Kurnianto; Budi Hariono; Sri Hartati (Jurnal Ilmiah Inovasi, 2018)
Uber Gadung (Dioscorea Hispida dennst) is a tuber plant that can produce glucomannan. Chemically, glucomannan is a non-ionic hydrochloric polysaccharide compound, having a high molecular weight of 9.0x105gmol-1atau2.7x105-1.1x106Dalton. The current problem is not done to the mass balance calculation at the end of the product being the processing base at the agroindustry level. The study consists of 3 main stages, including: (i) sampling; (ii) Product fractionation and drying; (iii) Economic extraction and calculation. The results showed that the calculation of the mass balance of treatment difference in mesh size gives the result that the larger the size (smaller particle size), resulting in less glucomannan. The fraction of glucomannan flour which passes 40-60 mesh sieve produces the highest glucomannan content compared to other particle size. The particle size treatment has significant effect on glucomannan, starch, crude fiber, water, density of kamba, viscosity, pH, and weight percentage. The highest yield is found in 40-60 mesh flour mung, while the highest starch and crude fiber content is in the size <100mesh. The highest added value is obtained from the processing into glucomannan with the value of Rp 650.000 / 100kg, as well as the profit of 86.67 percent. While the value of the lowest profits on the processing of gadung tuber into a dry chip.Â Keywords : Uber Gadung, glucomannan, dry chip